Improving The Ability To Write Personalized With Imagination Strategy In Class X Students Of SMK TPI Al Hasanah - Sukron Agus Hutagaol (UMSU, 2020)
Imagination strategy is a learning strategy that aims to enable students to develop the ability to focus and reflect. The steps for applying the Imagination strategy begin with (1) introducing the tofik that will be discussed, (2) then assigning students to close their eyes, (3) doing warm-up exercises to open their